Relationship Between Nutritional Status and Hemodialysis Therapy in Patients With Chronic Kidney Disease at Adam Malik Medan Hospital, Indonesia - Muhammad Siddik Nasution; Sumi Ramadani; Edy Ardiansyah; Deryne Anggia Paramita (Sumatera Medical Journal, 2025)
Background: One of the measures taken to control chronic kidney failure is through the hemodialysis procedure. Hemodialysis therapy can cause various side effects in patients, one of which is the risk of decreased nutritional status which can result in malnutrition. When the nutritional status of kidney failure patients worsens, the quality of life also decreases. Objective: This study aimed to determine the relationship between nutritional status and hemodialysis therapy at Haji Adam Malik General Hospital, Medan. Methods: This research was conducted from February to October 2024. This research is an analytical observational study using a cross sectional study design. The sample taken in this study was 80. Data was obtained from medical records at H. Adam Malik General Hospital, Medan. Results: The correlation test with the Chi-square test showed no relationship between Body Mass Index and several criteria, namely: Gender (p=0.645), age (p=0.410), creatinine (p=0.296), urea (p=0.296), albumin (p=0.315). Conclusion: There is no relationship between BMI and age, gender, albumin levels, creatinine levels and albumin levels in hemodialysis patients at H. Adam Malik General Hospital, Medan. The majority of patients undergoing hemodialysis at H. Adam Malik General Hospital Medan have a normal BMI (66%).